Relationship between Stress Level and Tension Type Headache among Medical Study Program, Faculty of Medicine, Mulawarman University - Bilahmar, Saphira Qayyum; Hutahaean, Yetty Octavia; Nugroho, Hary (Fakultas Kedokteran, 2022)
Background: Tension Type Headache (TTH) is the most common type of primary headache. TTH has a major impact on the productivity and social activities of the sufferers, especially students. The most common risk factor for TTH is stress, risk of getting TTH increased along with the stress level. Aims: This study aims to determine the relationship between stress levels and TTH among students of the Medical Study Program, Faculty of Medicine, Mulawarman University. Methods: A questionnaire-based cross-sectional study was conducted among Medical Study Program, Faculty of Medicine, Mulawarman University. The stress levels in this study were measured with the Perceived Stress Scale-10 (PSS-10) questionnaire. The incidence of TTH was assessed with the Headache Screening Questionnaire-Dutch Version (HSQ-DV). 217 respondents from the academic year 2018-2021 carried out with stratified random sampling technique.Results: The results showed that the majority of respondents experienced moderate stress (82.5%) and TTH was 54.4%. Bivariate analysis using the Chi-Square obtained p-value 0,565. Conclusions: There was no relationship between stress level and the incidence of TTH among students of the Medical Study Program, Faculty of Medicine, Mulawarman University.